Evaluation of The Quality of Gojek Online Transportation Driver Services Based on Customer Satisfaction Level in The City of Surabaya - Adilah, Fira; Al Fatih, Muhammad; Ahmed Muse, Abdurrahim; Amrozi, Yusuf (KH. A. Wahab Hasbullah University, 2024)
In the city of Surabaya, the use of online transportation applications is increasing and has become one of the popular transportation options. With the increase in public interest in the use of online transportation, various companies are competing with each other to further innovate in the process of developing online transportation applications. PT. Go-Jek Indonesia is one of the online motorcycle taxi companies that claims to be able to provide practical and fast services in the midst of congestion problems faced by people in several cities. This study aims to evaluate the quality of Gojek online transportation driver services based on the level of customer satisfaction in the city of Surabaya. The method used in this study uses a qualitative method. The data collection techniques carried out in this study used interview techniques and document studies. From the results of interviews and document studies in this study, it can be concluded that the service provided by Gojek drivers to passengers is of good quality so that it provides satisfaction to customers as expected. Although some of them said they were satisfied with the service that had been provided by the driver, there were still some improvements that needed to be made and improved for the performance of the Gojek company in order to improve or improve the company's brand image.